KECERDASAN EMOSIONAL PESERTA DIDIK DI SD TAKHASSUS ALQURAN KALIBEBER WONOSOBO - Ayu Sholina; Fajar Dwi Mukti (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2019)
This study presents the level of emotional intelligence both in terms of interpersonal and intrapersonal abilities of students at SD Takhassus al-Quran Kalibeber Wonosobo. The theory used in this study is the theory of emotional intelligence from Daniel Goleman. The purpose of this study was to examine the level of emotional intelligence of students in class VI B SD Takhassus AlQuran Kalibeber Wonosobo. The research method used in this study is a mixed method method with a concurrent embedded design model. Data collection techniques used are emotional intelligence scale, observation, and interviews. The results showed that: The level of emotional intelligence of students in class VI B SD Takhassus Al-Quran Kalibeber Wonosobo was very high (63.33%), this was proven from the results of the analysis that the researchers had done.